Old and new hypotheses about the homology of the compound bones from the cheek and otico-occipital regions of the anuran skull - Alcalde, Leandro (2013)
We have studied the larval development of compound bones from the otico-occipital and cheek regions in species of the neobatrachian genera Batrachyla, Hylorina, Leptodactylus, Odontophrynus and Pleurodema. Comparisons were made using a set of Ambystoma spp. (Caudata) and Ceratophrys ornata (Anura; Ceratophryidae) larvae. As with previous studies, we verified the compound nature of the exoccipital (two centres, anurans only), frontoparietal (one centre, most anurans and Ambystoma - three centres, some anurans), and squamosal (two centres, all anurans and Ambystoma) bones. We discuss old and new homology hypotheses for each of the compound bone centres in the context of the most widely accepted scenario of lissamphibian origins and relationships, i.e. a monophyletic Lissamphibia that contains the clade Batrachia (Caudata + Anura) and the most divergent Gymnophiona. Our findings have a direct impact on our understanding of the composition of the skull in Lissamphibia. We recognize the presence of the following bones: (1) opisthotic (fused to the exoccipital) and tabular (fused to the squamosal) in Batrachia (Anura + Caudata); and (2) supratemporal (fused to the parietal portion of the frontoparietal) in Anura. Separate centres of the parietal were found only in Pleurodema.